Mengungkap Jaringan dan Taktik Baru: Peran Ditreskrimsus Polda Sumatera Barat dalam Memerangi Kejahatan Perjudian Online - Cyta Sucy Marrismawati; Hendra Suherman; Deaf Wahyuni Ramadhani (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
Article 27 Paragraph (2) jo. 45 Paragraph (2) of the ITE Law regulates Online gambling. The handling of Online Gambling is the authority of Ditreskrimsus. Research Objectives To analyze the role of Ditreskrimsus in law enforcement on online gambling crimes. And To explore the obstacles encountered by Ditreskrimsus in enforcing the law on online gambling crimes. This type of research uses a socio-legal approach. The results of the study to The Directorate of Criminal Investigation of the West Sumatra Regional Police have played a good role in enforcing the law of online gambling; the obstacles encountered by the Ditreskrimsus of the West Sumatra Regional Police in enforcing the law on online gambling crimes are internal and external constraints.